Análise de dados com Power BI: um estudo de caso aplicado ao sistema de chamados GLPI em uma empresa do setor agropecuário - BARROS, José Paulo Silva (2024)
This work presents a detailed case study on data analysis using the Power BI tool, applied to the GLPI call system in a company in the agricultural sector. The study focused on understanding how Power BI can be used to improve IT management and support, highlighting its benefits and challenges. The research involved the ETL (Extract, Transform, Load) process, construction of several indicators and analysis of the results. The relevance of Power BI is also highlighted in its ability to provide valuable insights to improve strategic management.